2012
DOI: 10.1016/j.pec.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Three types of ambiguity in coding empathic interactions in primary care visits: Implications for research and practice

Abstract: Objective To describe three methodological challenges experienced in studying patients’ expressions of emotion in a sample of routine ambulatory medical visits, and the research and practice implications of these challenges. Methods Qualitative analysis of empathic cues in audio-taped and transcribed periodic health examinations of adult patients (n=322) in an integrated delivery system. The empathic and potential empathic opportunities methodology was used. Results Identifying emotional cues that constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…As previously suggested (31), these findings imply that a deeper understanding of the psychosocial burden of RA will enable health care providers to better manage or prevent patient-provider discordance. However, addressing this issue may present challenges because providers may not recognize psychosocial cues that patients present (32,33). When patients voice distress or other negative affective tones during rheumatology visits, their adherence to recommended treatments is predictably lower over time (34).…”
Section: Discussionmentioning
confidence: 99%
“…As previously suggested (31), these findings imply that a deeper understanding of the psychosocial burden of RA will enable health care providers to better manage or prevent patient-provider discordance. However, addressing this issue may present challenges because providers may not recognize psychosocial cues that patients present (32,33). When patients voice distress or other negative affective tones during rheumatology visits, their adherence to recommended treatments is predictably lower over time (34).…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Stone et al, the application of strict coding rules, according to which expressions either are or are not coded as emotional expression, may imply that subtle expressions of emotion are not coded as cues and are lost to analysis [96]. Interestingly, when Kale et al compared a qualitative discourse analysis with VR-CoDES, they found some expressions which they considered expressions of emotions that were not coded as cues in VR-CoDES [24].…”
Section: Detailed Classification Of Indirect and Explicit Expression mentioning
confidence: 99%
“…Mercer, Maxwell, Heaney, & Watt, 2004;Mercer, McConnachie, Maxwell, Heaney, & Watt, 2005). Issues arising from the use of these instruments have been reviewed by Stone, Tai-Seale, Stults, Luiz, and Frankel (2012), who point out that patients may present emotion cues in different ways, and that emotion episodes can vary a great deal in terms of length and intensity. These factors introduce complexity and ambiguity to the task of rating emotion events in real-life healthcare environments.…”
Section: Issues Associated With the Challenge Of Responding To Expresmentioning
confidence: 99%